PENGARUH STRES DAN KONFLIK KERJA TERHADAP KINERJA PEGAWAI PADA DINAS LINGKUNGAN HIDUP KOTA PALU - Maskun, Maskun (Fakultas Ekonomi Universitas Tadulako, 2016)
This study aims to determine the influence of work stress and work conflict on employee performance in The Environmental Office of Palu City. Method of study is descriptive. Yype of data is qualitative and quantitative data from primary and secondary data. Data analysis technique is multiple linear regression analysis. The result of hypothesis analysis and testing conclude that: (1) regression test shows sig. f equals to 0.003<0.05, which can be interpreted that work stress and work conflict simultaneously have positive and significant influence on employee performance; (2) regression test shows that job stress has significance level t sig. of (0.029) <? (0.05), and work conflict has significance level t sig. of (0.007) <? (0.05), which means that work stress and work conflict partially have positive and significant influence on employee performance.